HUBUNGAN POWER OTOT TUNGKAI DENGAN ACCURACY SMASH BOLAVOLI PADA SISWA PUTRA EKSTRAKURIKULER BOLAVOLI MAN 1 MUARA FAJAR PEKANBARU - M. Rohim, M. Rohim; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study used leg muscle strength with accuracy of volley ball smash on students of man extracurricular volley ball MAN 1 Muara Fajar Pekanbaru. The goal is to find out how much muscle strength with the accuracy of volley ball smash on students son extracurricular volley ball MAN 1 Muara Fajar Pekanbaru. This research technique using total sampling technique with sample number 12 student. This form of research is free. Instruments that are vertical jump and volley ball smash test. Then, the test data using the normality test, the product test of noble moments, test significant Î± = 0.05. Normality test of variable X, L0max (0,1839) <Ltable (0,242), and test of normality of variable Y, L0max (0,1517) <Ltable (0,242) in other words 95% confidence level normal data and research conclusion show: significant relationship between leg muscle strength relationship with volley ball smash accuracy, with general r = 0.6439 where rcount > rtable or 0.6439> 0.602. And relationships are strongly categorized. Thus, Ha is accepted.Keywords: Leg Muscle Strength, volley ball Smash